Performance Analysis of 2022 Women’s European Football Champion England National Team - Gizem Başkaya (Türk Spor ve Egzersiz Dergisi)
After big organizations in football or at the end of the season, researchers definitely examine the game systems of successful teams, the technical-tactical parameters of successful and unsuccessful teams, the differences and the performances of the athletes. In this direction, this study was conducted to analyze the England National Team, which was the champion in the 2022 Women's European Football Championship, in terms of different variables. Research data were obtained from the UEFA official website. The number of goals scored and conceded in competitions, the distribution of goals according to time periods, the region of the goal scored, the way the goals occur, the position of the goal scorer, the percentage of possession of the ball during the first half and throughout the match, the duration of the ball in the game, the number of passes, The number and percentage of successful passes, corner kick, offside technical-tactical parameters and the average total distance traveled by the team, the evaluation of substitution rights and the effect of the first goal on the result parameters were analyzed. The obtained data were recorded in SPSS 23 package program and interpreted by calculating frequency and percentage values. It was determined that the England national team scored a total of 22 goals with an average of 3.67 goals per match, and 2 goals were scored in their own goal with an average of 0.33 goals per game. Considering the time frame in the competitions, the England National Team scored 45.5% (10 goals) of the 22 goals in the first half, 45.5% (10 goals) in the second half, and the remaining 2 goals in the 1st and 2nd overtime periods; It has been revealed that he conceded 2 of his goals in the second half. 86% of the goals scored were from within the penalty area and most goals were scored from the 3rd area of the penalty area (13, 59.1%); 54.5% (12 goals) of these goals were scored as a result of organized attack; it was determined that the players who scored the most goals (8 goals, 36.4%) were the players in the wing position. The England national team, which has the ball at the rate of 57% per game, kept the ball in the game for 29 minutes and 33 seconds in 90 minutes; It has been determined that the percentage of successful pass is 84% and the average percentage of ball possession is 57%. It is also stated that the total distance traveled by the team per match is 116.6 km has been revealed. Based on these results, coaches; use the 3rd zone, which is the critical zone in the penalty area in terms of offense, more effectively; In terms of defense, it can be suggested that these regions be defended more effectively. In addition, considering that the most important factor determining the result in football is goals and that these goals are the result of organized attacks, it is important that the football players other than the strikers contribute to the score, and that the organizational studies are important, therefore it is necessary to plan the technical-tactical studies of the teams accordingly. is thought to be useful.